A method for preparing boehmite using industrial-grade aluminum hydroxide as raw material
By using industrial-grade aluminum hydroxide and using ball milling, sand milling, hydrothermal reaction and other processes, the problems of high cost and low purity of boehmite in the existing technology are solved, and high-purity and low-cost boehmite preparation are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202310499313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-05
AI Technical Summary
In the prior art, the cost of using high-purity aluminum hydroxide to prepare boehmite is relatively high, and the content of the prepared boehmite is relatively high and the purity is low.
High-purity boehmite is prepared by using industrial grade aluminum hydroxide as raw material and by ball milling, sand milling, hydrothermal reaction and other processes. The method includes mixing industrial grade aluminum hydroxide with deionized water, abrasive agent, etc., performing ball milling and sanding, adjusting pH, performing hydrothermal reaction and ceramic membrane washing, and finally performing drying to obtain boehmite.
It significantly reduces the cost of boehmite preparation, improves the uniformity of boehmite purity and particle size distribution, and is suitable for industrial mass production.
Smart Images

Figure CN116514151B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation, and in particular to a method for preparing boehmite by taking industrial-grade aluminum hydroxide as a raw material. Background Art
[0002] This section provides background information related to the present application which does not necessarily constitute prior art.
[0003] Boehmite, also known as soft water stone, has a structural formula of γ-AlOOH and is widely used in catalyst carriers, polishing abrasives, flame retardant materials, etc. There are many methods for preparing boehmite, such as the Bayer process, hydrolysis method and sol-gel method. At present, the following method is more commonly used to prepare boehmite: a mixture of aluminum hydroxide and water is ball-milled into aluminum hydroxide slurry, and then prepared into a suspension, and then a hydrothermal reaction is performed to prepare boehmite.
[0004] However, in the above-mentioned method for preparing boehmite, aluminum hydroxide (Al(OH)3) with a purity of more than 99.5%, a D50 particle size of less than 3 um, a Na content of no more than 1000 ppm, a Fe content of no more than 50 ppm, and a Cu content of no more than 5 ppm is mainly used as a raw material, but this method has the following technical problems:
[0005] 1. Since the purity requirement of the aluminum hydroxide raw material is high, the cost of the aluminum hydroxide raw material is high, which in turn leads to a high cost for preparing boehmite;
[0006] 2. The boehmite finally prepared by this method has a D50 particle size of 0.6-2.5 μm, a Na content of no more than 500 ppm, a Fe content of no more than 50 ppm, and a Cu content of no more than 5 ppm. Therefore, the boehmite prepared by this method has a high content of impurities such as Na, Fe, and Cu and a low purity.
[0007] From the perspective of reducing the cost of preparing boehmite, industrial-grade aluminum hydroxide can be used as a raw material to reduce the cost of raw materials. However, industrial-grade aluminum hydroxide has the following technical problems that prevent it from being used in preparing boehmite:
[0008] Industrial-grade aluminum hydroxide has a purity of more than 98%, a D50 particle size of about 100um, a Na content of not less than 1000ppm, a Fe content of not less than 50ppm, and a Cu content of not less than 5ppm. Therefore, industrial-grade aluminum hydroxide has the characteristics of coarse particle size, high impurity content, and complex impurity composition, making it impossible to use industrial-grade aluminum hydroxide to prepare boehmite with good dispersibility, good particle size distribution, uniform morphology, high purity, and high crystallinity. Summary of the invention
[0009] In view of the technical problems existing in the prior art, the present invention provides a method for preparing boehmite using industrial-grade aluminum hydroxide as a raw material. The method uses industrial-grade aluminum hydroxide as a raw material to prepare high-purity boehmite. The boehmite finally prepared by the method has a D50 particle size of 0.6-2.5um, a Na content of not more than 200ppm, a Fe content of not more than 10ppm and a Cu content of not more than 2ppm. Therefore, the boehmite prepared by the method can be used in the preparation of batteries.
[0010] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing boehmite using industrial-grade aluminum hydroxide as raw material, comprising the following steps:
[0011] The process of mixing industrial grade aluminum hydroxide, deionized water, a grinding aid, a penetrant, a defoamer and a pH regulator to obtain a first slurry;
[0012] The process of sequentially ball milling and sand milling the first slurry to obtain a second slurry;
[0013] The pH of the second slurry is adjusted to 4-5 and reacted for not less than 30 minutes to obtain a third slurry;
[0014] The process of feeding the third slurry into a ceramic membrane and washing it with deionized water having a temperature not lower than 40° C. to obtain a fourth slurry;
[0015] The process of filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry having a solid content of 20% to 35%;
[0016] The step of mixing the fifth slurry with sodium hydroxide and a dispersant and then subjecting the mixture to a hydrothermal reaction to obtain a sixth slurry containing boehmite;
[0017] The process of adjusting the pH of the sixth slurry to 4-6 and then adding a penetrant to obtain a seventh slurry;
[0018] The seventh slurry is fed into a ceramic membrane and washed with deionized water having a temperature not lower than 40° C. to obtain an eighth slurry;
[0019] The eighth slurry is dried to obtain boehmite.
[0020] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0021] 1. The method provided by the present invention uses industrial-grade aluminum hydroxide as raw material, which significantly reduces the cost of preparing boehmite;
[0022] 2. The impurity content of the boehmite prepared by the method provided by the present invention is significantly better than that of the currently commercially available boehmite.
[0023] The following is an explanation in conjunction with a specific implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings further illustrate the present invention, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.
[0025] Figure 1 This is a schematic flow chart of the method for preparing boehmite provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0027] The method for preparing boehmite provided by the present invention can not only use industrial-grade aluminum hydroxide as a raw material, but also use chemically pure, analytically pure or superior-grade aluminum hydroxide as a raw material. It should be noted that the industrial-grade aluminum hydroxide recorded in the embodiments of the present invention meets the following requirements: purity of more than 98%, D50 particle size of about 100um, Na content of not less than 1000ppm, Fe content of not less than 50ppm and Cu content of not less than 5ppm, and in addition to impurities of sodium (Na), iron (Fe) and copper (Cu), the composition of other impurities contained in industrial-grade aluminum hydroxide prepared by different preparation methods is also different, and the industrial-grade aluminum hydroxide may also contain one or more of the impurities of zinc (Zn), silicon (Si), lead (Pb), calcium (Ca), lithium (Li), antimony (Sb) and magnesium (Mg).
[0028] The particle size and particle size distribution of solid particles are determined by the following method:
[0029] 1. Preparation of samples to be tested
[0030] Weigh 50 g of the solid particles to be tested, disperse them in 2 L of water, and disperse them evenly under stirring conditions (stirring speed of 2500 r / min, time of 2 min) to obtain a sample to be tested.
[0031] 2. Determination of particle size and particle size distribution
[0032] The particle size and particle size distribution of solid particles are measured by a laser particle size analyzer, comprising the following steps:
[0033] Turn on the laser particle size analyzer;
[0034] to light;
[0035] Set the parameters of the laser particle size analyzer, the measurement time is 10s, the background time is 12s, and the light shielding degree is 10%;
[0036] Add 800 mL of deionized water to the sampler of the laser particle size analyzer, and adjust the speed of the sampler stirrer of the laser particle size analyzer to 2500 r / min;
[0037] Background measurement: Measure tap water with a laser particle size analyzer. When the laser degree is ≥78%, the background measurement is completed and the background value is recorded.
[0038] Measurement of the sample to be tested: Add the sample to be tested into the sample injection stirrer of the laser particle size analyzer, and adjust the speed of the sample injection stirrer of the laser particle size analyzer to 2500r / min; when the light shielding degree of the laser particle size analyzer reaches 10%, stop the injection and start the measurement;
[0039] Data processing, using a laser particle size analyzer to obtain the particle size distribution results of the sample to be tested, as well as D10 (i.e., the particle size corresponding to 10% of the cumulative particle size distribution number of the sample), D50 (i.e., the median diameter, the particle size corresponding to 50% of the cumulative particle size distribution number of the sample) and D90 (i.e., the particle size corresponding to 90% of the cumulative particle size distribution number of the sample) values. After each batch of materials is mixed evenly, the measurement is repeated 7 times.
[0040] In the embodiment of the present invention, liquid chromatography-tandem mass spectrometry (LC-MS / MS) is used to detect the impurity content in the slurry.
[0041] The cavity height L of the conductivity test device for testing the slurry in the embodiment of the present invention is 0.25 cm, and the cross-sectional area S is 2.32 cm 2 , the theoretical volume is 0.58cm 3 , the conductivity of the slurry was measured using a conductivity test device using the following method:
[0042] 1. Use a pipette to accurately measure the slurry corresponding to the theoretical volume, and inject the slurry into the horizontally placed negative electrode shell until the slurry just fills the negative electrode shell;
[0043] 2. Snap the positive electrode shell onto the negative electrode shell horizontally, and set the sealing pressure of the sealing machine to 750kg / cm 2 , sealed by a sealing machine to form a slurry conductivity test body filled with slurry;
[0044] 3. Connect the positive and negative electrodes of the slurry conductivity test body to the positive and negative electrodes of the test fixture of the electrochemical workstation, respectively, and perform impedance test or electrochemical impedance test. Set the test frequency of the alternating current and the disturbance current amplitude or disturbance voltage amplitude, and test the impedance under different frequencies and different disturbance amplitudes. The test frequency range is 0.01Hz-10kHz;
[0045] 4. Calculate the conductivity of the slurry using the conductivity calculation formula. The conductivity calculation formula is σ = L / RS, where σ is the conductivity, L is the cavity height of the button battery shell, S is the cavity cross-sectional area of the button battery shell, and R is the impedance measured by the electrochemical workstation.
[0046] An embodiment of the present invention provides a method for preparing boehmite using industrial-grade aluminum hydroxide as a raw material, which specifically comprises the following steps:
[0047] Step 1: industrial grade aluminum hydroxide, deionized water, grinding aid, penetrant, defoamer and pH regulator are mixed to obtain a first slurry with a pH of 4-6 and a solid content of 10%-30%.
[0048] Since the particle size of industrial-grade aluminum hydroxide is coarse, it is not conducive to the subsequent removal of impurities and the synthesis of boehmite. The slurry is prepared by mixing industrial-grade aluminum hydroxide, deionized water, grinding aids, penetrants, defoamers and pH regulators, and then the subsequent ball milling-sand milling process is used to obtain particles with small particle size and uniform particle size distribution.
[0049] The solid content of the first slurry may be adjusted by adding deionized water.
[0050] The pH adjuster is used to adjust the pH of the first slurry. The pH value of the first slurry affects the subsequent ball milling and sand milling process mainly by: affecting the interaction between the grinding aid molecules and the particle surface by adjusting the surface electrical properties and positioning ions of the particles; affecting the rheological properties of the first slurry and the dispersibility between the particles by adjusting the viscosity of the first slurry. Preferably, the pH adjuster is nitric acid, hydrochloric acid or sulfuric acid.
[0051] Step 2: The first slurry is subjected to ball milling and sand milling in sequence to obtain the second slurry, and the ball milling time is 2-6 hours. The particles in the second slurry meet the following conditions: D50 is 1.0-2.5 μm and D90 is not greater than 5 μm. At this time, the particle quality of the second slurry is more uniform. In addition, the ball milling-sand milling process makes the particle size distribution of the particles of the second slurry narrower. The aluminum hydroxide with this particle size distribution obtains boehmite with ideal particle size and morphological characteristics after the subsequent hydrothermal reaction.
[0052] Since the particle size of industrial-grade aluminum hydroxide is coarse, if it is directly sand-milled without ball milling, the sand mill will easily become clogged. Therefore, it is necessary to first ball-mill the industrial-grade aluminum hydroxide for preliminary crushing.
[0053] The grinding aid can reduce the strength of the particles and improve the grindability of aluminum hydroxide by preventing "closing" and reducing the hardness of aluminum hydroxide during crack formation and expansion during ball milling and sand milling. Preferably, the grinding aid is triethanolamine, and the addition amount of triethanolamine is 0.3-0.5 mass parts based on 100 mass parts of industrial grade aluminum hydroxide.
[0054] Since the particle size of the particles obtained after ball milling and sand milling is small, the finer the particle size, the larger the specific surface area, and the viscosity of the second slurry will increase under the same solid content. Therefore, by adding a defoaming agent, the viscosity of the second slurry can be reduced, thereby improving the fluidity of the second slurry. In addition, the addition of a defoaming agent can make the suspension rate of the particles in the second slurry reach more than 96%, thereby improving the stability of the second slurry. The defoamer is preferably a surfactant containing a polyether group, and examples thereof include alkyl polyoxyalkylene ether, aryl polyoxyalkylene ether, alkyl aryl polyoxyalkylene ether, alkoxylated animal and / or vegetable fats and / or oils, fatty amine alkoxylates, fatty acid amide alkoxylates, fatty acid diethanolamide alkoxylates, polyoxyethylene sorbitan fatty acid esters, alkyl polyether sulfates, aryl polyether sulfates, alkyl aryl polyether sulfates, alkyl polyether sulfonates, aryl polyether sulfonates, alkyl aryl polyether sulfonates, alkyl polyether phosphates, aryl polyether phosphates, alkyl aryl polyether phosphates, glyceryl ether sulfonates, glyceryl ether sulfates, monoglyceride (ether) sulfates, fatty acid amide ether sulfates, polyoxyalkylene sorbitan fatty acid esters, and mixtures thereof. Based on 100 parts by mass of industrial grade aluminum hydroxide, the addition amount of the defoamer is 0.03-0.06 parts by mass.
[0055] Adding a grinding aid and a penetrant at the same time can produce a synergistic effect to improve the grindability of industrial-grade aluminum hydroxide, and can prevent the adhesion, agglomeration and adhesion of the fine particles of the second slurry to the grinding medium, can significantly improve the fluidity of the second slurry, improve the particle fineness of the second slurry, and reduce the crushing limit and the energy consumption of ball milling-sand milling. The penetrant is one of fatty alcohol polyoxyethylene ether, silicone (such as ethoxy-modified trisiloxane), alkylphenol polyoxyethylene ether, polyether, and phosphate compounds. Preferably, the penetrant is fatty alcohol polyoxyethylene ether (JFC). Based on 100 parts by mass of industrial-grade aluminum hydroxide, the addition amount of the penetrant is 0.3-0.5 parts by mass.
[0056] It should be noted that in step one and step two, since the pH of the first slurry is 4-6, during the ball milling and sand milling process of the first slurry, as the particle size of the aluminum hydroxide particles becomes finer, the specific surface area increases, that is, the reaction contact area increases, and some solid impurities are dissolved. Therefore, the process of preparing the second slurry is also regarded as the first step of impurity removal.
[0057] It should be noted that the particle size distribution in the second slurry will affect the particle size distribution of the boehmite finally prepared.
[0058] Step three, adjusting the pH of the second slurry to 4-5 and continuously stirring the reaction for 30-60 minutes to obtain a third slurry.
[0059] A pH adjuster is used to adjust the pH of the second slurry. The pH adjuster used in step three is the same as the pH adjuster used in step one, so as to avoid the introduction of other anions. The pH adjustment of the second slurry needs to meet the following requirements at the same time: avoid the dissolution of aluminum hydroxide; promote the dissolution of solid impurities. Since aluminum hydroxide is an amphoteric hydroxide, it is appropriate to avoid the pH of the second slurry being lower than 4; at the same time, if the pH of the second slurry is higher than 5, the solubility of solid impurities will be significantly reduced.
[0060] Step 4, feeding the third slurry into the ceramic membrane and washing it with deionized water at a temperature of 40-70°C until the slurry simultaneously meets the following conditions: conductivity less than 50us / cm, Cu content not more than 5ppm and Fe content not more than 20ppm, thereby obtaining a fourth slurry.
[0061] It was unexpectedly found that the use of deionized water at a temperature of not less than 40°C for washing can significantly reduce the amount of water used in the washing process, that is, the volume of deionized water required to prepare the fourth slurry using deionized water at a temperature of not less than 40°C is only 30%-50% of the volume of deionized water required to prepare the fourth slurry using deionized water at room temperature. In addition, reducing the amount of water used in the washing process can increase the solid content of the fifth slurry prepared subsequently.
[0062] During the washing process of the third slurry, since the retention pore size of the ceramic membrane is smaller than the aluminum hydroxide particles suspended in the third slurry, the aluminum hydroxide particles are completely retained by the ceramic membrane, while the dissolved impurities, grinding aids, penetrants, defoaming agents, etc. in the third slurry will pass through the ceramic membrane, thereby realizing the second step of impurity removal.
[0063] Step 5, filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry with a solid content of 20%-35%, so that the solid aluminum hydroxide particles are completely trapped in the concentrated liquid;
[0064] The ceramic membrane used in step 4 and step 5 has an average pore size of 0.02-0.1 μm, preferably 0.02-0.05 μm; the ceramic membrane is composed of a support and a separation layer covering the support, the support material is α-alumina with a purity greater than 99wt%, the separation layer material is a mixture of one or more of aluminum oxide, zirconium oxide, and titanium oxide, the separation layer thickness is 10-100 μm, preferably 10-20 μm; the porosity of the ceramic membrane is greater than 37%. The membrane element adopts an internal pressure tubular membrane structure.
[0065] In step five, the filtration pressure of the ceramic membrane filtration and concentration process is 0.05-0.5Mpa, preferably 0.05-0.3MPa; the membrane surface flow rate is 1-5m / s, preferably 2.5-3.5m / s; the temperature is 30-60°C. And periodic backwashing can be performed during the ceramic membrane filtration and concentration process. The backwashing medium for periodic backwashing is deionized water at 40-70°C, the backwashing cycle is 15-60min, the backwashing time is 10-15s, and the backwashing pressure is 0.4-0.7MPa. The narrow pore size distribution of the ceramic membrane makes the pore size accuracy of the ceramic membrane relatively high. By selecting a membrane with a suitable pore size, the clogging of the membrane pores can be avoided. At the same time, the high strength of the ceramic membrane can not only enable it to withstand higher recoil pressures without destroying the membrane pores.
[0066] It is unexpectedly found that if deionized water below 40°C is used for washing in step 4, the solid content of the fifth slurry obtained in step 5 is less than 20%, which reduces the efficiency of preparing boehmite. If the solid content of the fifth slurry is greater than 35%, the fifth slurry will be too viscous and have poor fluidity.
[0067] Step six, mixing the fifth slurry with sodium hydroxide and a dispersant, and then subjecting the mixture to a hydrothermal reaction to obtain a sixth slurry containing boehmite.
[0068] Sodium hydroxide is added to the fifth slurry to adjust the pH to 8-10. The sodium hydroxide may be prepared into a solution before adding it to the fifth slurry.
[0069] Wherein dispersant is at least one of polyethylene glycol (PEG), polyethylene glycol, sodium dodecylbenzene sulfonate, ammonium polyacrylate, polyvinyl alcohol, C1-C9 organic acid dispersant. C1-C9 organic acid dispersant is one or more of formic acid, acetic acid, propionic acid, n-butyric acid, isobutyric acid, n-valeric acid, isovaleric acid, caproic acid, enanthic acid, octanoic acid and nonanoic acid. Based on 100 parts by mass of industrial grade aluminum hydroxide, the addition amount of dispersant is 0.1-0.3 parts by mass. From the viewpoint of suppressing heterogeneous generation and avoiding particle size coarsening during hydrothermal reaction, preferably, dispersant is PEG.
[0070] The hydrothermal reaction process is as follows: the fifth slurry is mixed with sodium hydroxide and a dispersant and placed in a reactor, and then steam at a pressure of 1Mpa is introduced, heated to a temperature of 180-220°C, and the pressure is controlled at 1.2Mpa for high-temperature reaction. After 1-4 hours of high-temperature reaction, the sixth slurry containing boehmite is obtained by cooling to 80°C. The boehmite obtained in this way is manufactured by a hydrothermal reaction in which a suspension containing aluminum hydroxide particles is heated under high pressure to crystallize it. The prepared boehmite satisfies: D50 is 0.6-2.5um and D90 is not greater than 3.8μm and the specific surface area is 6-10m 2 / g. The boehmite obtained after the hydrothermal reaction has the advantages of narrow particle size distribution, uniform morphology and good dispersibility.
[0071] From the perspective of reducing production costs, the cooling water used in the cooling stage of the hydrothermal reaction can be used as washing water after being heated.
[0072] Step seven, adjusting the pH of the sixth slurry to 4-6 and then adding a penetrant to obtain a seventh slurry.
[0073] It should be noted that a pH adjuster is used to adjust the pH of the sixth slurry, and the pH adjuster used in step 7 is the same as the pH adjuster used in step 1, so as to avoid the introduction of other anions. The penetrant added to the sixth slurry is the same as the penetrant recorded in step 1. Based on 100 parts by mass of boehmite, the amount of the penetrant added is 0.3-0.5 parts by mass.
[0074] Due to the hydrothermal reaction, the sixth slurry contains insoluble solid particles generated by impurities in addition to boehmite, such as impurity copper and impurity cobalt that generate insoluble delafossite oxides through hydrothermal reaction, impurity copper and impurity cobalt that generate insoluble calcium copper complexes through hydrothermal reaction, impurity copper, impurity silicon and impurity iron that generate insoluble cobalt silicate copper iron complexes through hydrothermal reaction, impurity iron that generates insoluble mica iron oxide through hydrothermal reaction, etc. Therefore, it is necessary to adjust the pH of the sixth slurry to 4-6 to dissolve the insoluble solid particles generated by impurities.
[0075] Step eight, the seventh slurry is fed into the ceramic membrane and washed with deionized water at a temperature of 40-70°C until the slurry simultaneously meets the following conditions: conductivity less than 20us / cm, Na content not more than 200ppm, Cu content not more than 2ppm and Fe content not more than 10ppm, thereby obtaining the eighth slurry.
[0076] The ceramic membrane used in step 7 is the same as that used in step 4. The added penetrant can significantly improve the washing efficiency and shorten the washing time. Step 7 can be regarded as the impurity removal treatment of the third step.
[0077] Step nine, drying the eighth slurry to obtain boehmite. Specifically, the eighth slurry is dried by a spray drying process, and the air inlet temperature is controlled at 230-280° C. and the outlet temperature is controlled at 95-105° C. to ensure that the moisture content of the boehmite is not greater than 0.25%.
[0078] [Example 1]
[0079] like Figure 1 As shown, this embodiment provides a method for preparing boehmite using industrial-grade aluminum hydroxide as a raw material, which specifically comprises the following steps:
[0080] Step 1, industrial grade aluminum hydroxide, deionized water, triethanolamine, JFC, alkyl polyoxyalkylene ether and 0.2 mol / L dilute sulfuric acid are mixed to obtain a first slurry with a pH of 4 and a solid content of 10%;
[0081] Step 2, the first slurry is subjected to ball milling and sand milling in sequence to obtain a second slurry, and the ball milling time is 2 hours;
[0082] Step 3, adjusting the pH of the second slurry to 4 using 0.1 mol / L dilute sulfuric acid and continuing to stir the reaction for 30 minutes to obtain a third slurry;
[0083] Step four, feeding the third slurry into the ceramic membrane and washing it with deionized water at a temperature of 40°C until the slurry simultaneously meets the following conditions: conductivity less than 50 us / cm, Cu content not more than 5 ppm and Fe content not more than 20 ppm, thereby obtaining a fourth slurry.
[0084] Step 5, filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry with a solid content of 20%;
[0085] Step six, adjusting the pH of the fifth slurry to 8 using a 1.0 mol / L sodium hydroxide solution, then adding PEG, mixing, and performing a hydrothermal reaction to obtain a sixth slurry containing boehmite;
[0086] Step 7, adjusting the pH of the sixth slurry to 4 using 0.1 mol / L dilute sulfuric acid, and then adding JFC to obtain a seventh slurry;
[0087] Step eight, feeding the seventh slurry into the ceramic membrane and washing it with deionized water at a temperature of 40° C. until the slurry simultaneously satisfies: conductivity less than 20 us / cm, Na content not more than 200 ppm, Cu content not more than 2 ppm and Fe content not more than 10 ppm, thereby obtaining an eighth slurry;
[0088] Step nine, drying the eighth slurry to obtain boehmite with a moisture content of no more than 0.25%.
[0089] [Example 2]
[0090] This embodiment provides a method for preparing boehmite using industrial-grade aluminum hydroxide as a raw material, which specifically comprises the following steps:
[0091] Step 1, mixing industrial grade aluminum hydroxide, deionized water, triethanolamine, JFC, alkyl polyoxyalkylene ether and 0.2 mol / L dilute sulfuric acid to obtain a first slurry with a pH of 6 and a solid content of 30%;
[0092] Step 2, the first slurry is subjected to ball milling and sand milling in sequence to obtain a second slurry, and the ball milling time is 6 hours;
[0093] Step 3, adjusting the pH of the second slurry to 5 using 0.1 mol / L dilute sulfuric acid and continuing to stir the reaction for 60 min to obtain a third slurry;
[0094] Step four, feeding the third slurry into the ceramic membrane and washing it with deionized water at a temperature of 70°C until the slurry simultaneously meets the following conditions: conductivity less than 50 us / cm, Cu content not more than 5 ppm and Fe content not more than 20 ppm, thereby obtaining a fourth slurry.
[0095] Step 5, filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry with a solid content of 35%;
[0096] Step six, adjusting the pH of the fifth slurry to 10 using a 1.0 mol / L sodium hydroxide solution, then adding PEG, mixing, and performing a hydrothermal reaction to obtain a sixth slurry containing boehmite;
[0097] Step 7, adjusting the pH of the sixth slurry to 6 using 0.1 mol / L dilute sulfuric acid, and then adding JFC to obtain a seventh slurry;
[0098] Step eight, feeding the seventh slurry into the ceramic membrane and washing it with deionized water at a temperature of 70° C. until the slurry simultaneously satisfies: conductivity less than 20 us / cm, Na content not more than 200 ppm, Cu content not more than 2 ppm and Fe content not more than 10 ppm, thereby obtaining an eighth slurry;
[0099] Step nine, drying the eighth slurry to obtain boehmite with a moisture content of no more than 0.25%.
[0100] [Example 3]
[0101] This embodiment provides a method for preparing boehmite using industrial-grade aluminum hydroxide as a raw material, which specifically comprises the following steps:
[0102] Step 1, industrial grade aluminum hydroxide, deionized water, triethanolamine, JFC, alkyl polyoxyalkylene ether and 0.2 mol / L dilute sulfuric acid are mixed to obtain a first slurry with a pH of 5 and a solid content of 20%;
[0103] Step 2, the first slurry is subjected to ball milling and sand milling in sequence to obtain a second slurry, and the ball milling time is 4 hours;
[0104] Step 3, adjusting the pH of the second slurry to 4.5 using 0.1 mol / L dilute sulfuric acid and continuing to stir the reaction for 50 minutes to obtain a third slurry;
[0105] Step four, feeding the third slurry into the ceramic membrane and washing it with deionized water at a temperature of 60°C until the slurry simultaneously meets the following conditions: conductivity less than 50 us / cm, Cu content not more than 5 ppm and Fe content not more than 20 ppm, thereby obtaining a fourth slurry.
[0106] Step 5, filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry with a solid content of 30%;
[0107] Step six, adjusting the pH of the fifth slurry to 9 using a 1.0 mol / L sodium hydroxide solution, then adding PEG, mixing, and performing a hydrothermal reaction to obtain a sixth slurry containing boehmite;
[0108] Step 7, adjusting the pH of the sixth slurry to 5 using 0.1 mol / L dilute sulfuric acid, and then adding JFC to obtain a seventh slurry;
[0109] Step eight, feeding the seventh slurry into the ceramic membrane and washing it with deionized water at a temperature of 60° C. until the slurry simultaneously satisfies: conductivity less than 20 us / cm, Na content not more than 200 ppm, Cu content not more than 2 ppm and Fe content not more than 10 ppm, thereby obtaining an eighth slurry;
[0110] Step nine, drying the eighth slurry to obtain boehmite with a moisture content of no more than 0.25%.
[0111] The physical parameters of the boehmite prepared in Examples 1-3 and commercially available boehmite are shown in Table 1.
[0112] Table 1
[0113]
[0114] The data in Table 1 show that although the method for preparing boehmite provided by the present invention uses industrial-grade aluminum hydroxide as a raw material, the purity and quality of the boehmite finally prepared are better than those of boehmite prepared by existing methods, especially considering that existing methods for preparing boehmite generally use high-purity aluminum hydroxide as a raw material. Therefore, the method for preparing boehmite provided by the present invention has a significant cost advantage over existing methods for preparing boehmite, and is suitable for industrial mass production of boehmite.
[0115] [Example 4]
[0116] In order to study the effect of the ball milling-sand milling process in step 2 of the method for preparing boehmite provided by the present invention on the particle size distribution of the aluminum hydroxide particles in the second slurry, the following test was designed:
[0117] The test sample is the first slurry described in Example 3. 30 portions of the first slurry of the same volume were divided into three groups, each with the same number of portions, and then one group was subjected to separate ball milling, one group was subjected to separate sand milling, and the remaining group was subjected to ball milling-sand milling. The particle size distribution of particles obtained by different treatment methods is shown in Table 2.
[0118] The data in Table 2 show that the aluminum hydroxide particles can obtain a narrower particle size distribution through ball milling and sand milling treatment in sequence.
[0119] Table 2
[0120]
[0121] [Example 5]
[0122] In order to study the effect of deionized water at different temperatures on the washing effect in the method for preparing boehmite provided by the present invention, the following test was designed:
[0123] 1. The test sample is the third slurry obtained in step 3 as described in Example 3. The third slurry is fed into the ceramic membrane and washed with deionized water of the same volume but different temperatures. The impurity content in the washed slurry is then tested. The results are shown in Table 3.
[0124] 2. The test sample is the seventh slurry obtained through step seven in Example 3. The seventh slurry is sent into the ceramic membrane and washed with deionized water of the same volume but different temperatures. Then, the impurity content in the washed slurry is tested. The results are shown in Table 4.
[0125] Table 3
[0126]
[0127] Table 4
[0128]
[0129] The data in Tables 3 and 4 show that the effects of deionized water of the same volume but different temperatures on washing and impurity removal are significantly different. Using deionized water at 40-70°C for washing can significantly improve the impurity removal effect.
[0130] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0131] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing boehmite using industrial grade aluminum hydroxide as raw material, characterized in that: The steps include: Step 1, mixing industrial grade aluminum hydroxide, deionized water, a grinding aid, a penetrant, a defoamer and a pH regulator to obtain a first slurry; Step 2, ball milling and sand milling the first slurry in sequence to obtain a second slurry; Step 3, adjusting the pH of the second slurry to 4-5 and reacting for not less than 30 minutes to obtain a third slurry; Step 4, feeding the third slurry into the ceramic membrane and washing it with deionized water at a temperature not lower than 40° C. to obtain a fourth slurry; Step 5, filtering and concentrating the fourth slurry in the ceramic membrane to obtain a fifth slurry with a solid content of 20%-35%; Step six, mixing the fifth slurry with sodium hydroxide and a dispersant and then performing a hydrothermal reaction to obtain a sixth slurry containing boehmite; Step seven, adjusting the pH of the sixth slurry to 4-6 and then adding a penetrant to obtain a seventh slurry; Step eight, feeding the seventh slurry into a ceramic membrane and washing it with deionized water having a temperature not lower than 40° C. to obtain an eighth slurry; Step nine, drying the eighth slurry to obtain boehmite; The grinding aid is triethanolamine, and the addition amount of the triethanolamine is 0.3-0.5 parts by mass based on 100 parts by mass of industrial grade aluminum hydroxide; The penetrant is fatty alcohol polyoxyethylene ether.
2. The method according to claim 1, characterized in that In the step 1, based on 100 parts by mass of the industrial grade aluminum hydroxide, the amount of the penetrant added is 0. 3-0.5 parts by mass.
3. The method according to claim 1, characterized in that In the step seven, based on 100 parts by mass of the boehmite, the added amount of the penetrant is 0.3-0.5 parts by mass.
4. The method according to claim 1, characterized in that: The defoamer is a surfactant containing a polyether group. Based on 100 parts by mass of industrial-grade aluminum hydroxide, the added amount of the defoamer is 0.03-0.06 parts by mass.
5. The method according to claim 1, characterized in that The pH adjuster is nitric acid, hydrochloric acid or sulfuric acid.
6. The method according to claim 1, characterized in that The dispersant is at least one of polyethylene glycol, polyethylene glycol, sodium dodecylbenzene sulfonate, ammonium polyacrylate, polyvinyl alcohol, and C1-C9 organic acid dispersants, and the C1-C9 organic acid dispersant is one or more of formic acid, acetic acid, propionic acid, n-butyric acid, isobutyric acid, n-valeric acid, isovaleric acid, hexanoic acid, heptanoic acid, octanoic acid, and nonanoic acid.
7. The method according to claim 6, characterized in that The dispersant is polyethylene glycol.
8. The method according to claim 1, characterized in that The temperature of the deionized water in step 4 is 40-70°C, and the temperature of the deionized water in step 8 is 40-70°C.
Citation Information
Patent Citations
Alpha-alumina micro-powder, preparation method and application thereof
CN111302368A
Preparation method of boehmite with low water absorption
CN112456525A